Revitalizing the Significance of Sumbang Duo Baleh in the Development of Social Ethics Among the Minangkabau Youth Generation - Agustina, Agustina; Elpalina, Srimutia; Azis, Adek Cerah Kurnia; Sugito, Sugito (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The social ethical crisis that hit the young generation today is a serious concern in the world of education and culture. Phenomena such as bullying, degradation of manners, and a decline in the sense of social responsibility are real symptoms of the weakening of moral values that should be formed from an early age. In the context of the Minangkabau community, the customary values contained in the Sumbang Duo Baleh are one of the sources of local wisdom that is rich in ethical guidelines and social conduct. This article aims to analyze the relevance of Sumbang Duo Baleh in the formation of social ethics of the younger generation, as well as offer a strategy for revitalizing these values so that they remain contextual in the modern era. The method used is a literature study with a descriptive qualitative approach, through the analysis of cultural documents, scientific literature, and reflection on cultural practices in the Minangkabau community. The results of the study show that the Baleh Duo Contribution, which consists of twelve ethical norms such as kato (speaking politely), cembang danga (listening well), sumcontribution karajo (being responsible for work), and incest (acting appropriately), has great potential as a guideline in shaping the social attitudes and character of the younger generation. However, these values are starting to be marginalized due to the lack of cultural literacy and the strong flow of global values. Therefore, the revitalization of these customary values needs to be carried out through synergy between schools, families, and indigenous peoples, with the support of digital technology as a medium for transforming values that are adaptive and attractive to Generation Z. The implications of this study show the need for a character education policy that is more based on local wisdom, as well as the development of culture-based learning media to strengthen the identity and integrity of the younger generation.